Joint report of SBI (Brazilian Society of Infectious Diseases), FEBRASGO (Brazilian Federation of Gynecology and Obstetrics Associations), SBU (Brazilian Society of Urology) and SBPC/ML (Brazilian Society of Clinical Pathology/Laboratory Medicine): recommendations for the clinical management of lower urinary tract infections in pregnant and non-pregnant women - Rossi,Patricia de (2020)
ABSTRACT Urinary tract infection (UTI) is a common condition in women. There is an increased concern on reduction of bacterial susceptibility resulting from wrongly prescribing antimicrobials. This paper summarizes the recommendations of four Brazilian medical societies (SBI - Brazilian Society of Infectious Diseases, FEBRASGO - Brazilian Federation of Gynecology and Obstetrics Associations, SBU - Brazilian Society of Urology, and SBPC/ML - Brazilian Society of Clinical Pathology/Laboratory Medicine) on the management of urinary tract infection in women.Asymptomatic bacteriuria should be screened at least twice during pregnancy (early and in the 3rd trimester). All cases of significant bacteriuria (≥105 CFU/mL in middle stream sample) should be treated with antimicrobials considering safety and susceptibility profile. In women with typical symptoms of cystitis, dipsticks are not necessary for diagnosis. Urine cultures should be collected in pregnant women, recurrent UTI, atypical cases, and if there is suspicion of pyelonephritis. First line antimicrobials for cystitis are fosfomycin trometamol in a single dose and nitrofurantoin, 100 mg every 6 hours for five days. Second line drugs are cefuroxime or amoxicillin-clavulanate for seven days. During pregnancy, amoxicillin and other cephalosporins may be used, but with a higher chance of therapeutic failure.In recurrent UTI, all episodes should be confirmed by urine culture. Treatment should be initiated only after urine sampling and with the same regimens indicated for isolated episodes. Prophylaxis options of recurrent UTI are behavioral measures, non-antimicrobial and antimicrobial prophylaxis. Vaginal estrogens may be recommended for postmenopausal women. Other non-antimicrobial prophylaxis, including cranberry and immunoprophylaxis, have weak evidence supporting their use. Antimicrobial prophylaxis may be offered as a continuous or postcoital scheme. In pregnant women, options are cephalexin, 250-500 mg and nitrofurantoin, 100 mg (contraindicated after 37 weeks of pregnancy). Nonpregnant women may use fosfomycin trometamol, 3 g every 10 days, or nitrofurantoin, 100 mg (continuous or postcoital).